Chemical composition, anti-inflammatory and cytotoxic activity of essential oils from two Luvunga species (L. scandens and L. hongiaoensis) from Vietnam - Trịnh, Thị Điệp (Taylor & Francis, 2023)
New essential oils (EOs) extracted from different parts of two Luvunga species (L. scandens and L. hongiaoensis) from Vietnam were investigated for their chemical composition, anti-inflammatory and cytotoxic activity. Sixty-nine total compounds were identified in the EOs by GC/MS. The major constituent of the leaf, fruit, and root EOs from L. scandens was β-caryophyllene (71.5%, 63.0%, and 31.5% respectively). The main compounds in L. hongiaoensis EOs were β-elemene (34.3% in leaf oil) and caryophyllene oxide (21.2% in root oil, 19.4% in stem oil). The EO from L. scandens fruits significantly inhibited nitric oxide production on LPS-induced RAW264.7 cells (IC50 = 37.95±2.76 g/mL). The EOs from L. hongiaoensis roots and L. scandens leaves and fruits exhibited cytotoxic activity against MCF-7, SK-LU-1, and HepG2 (IC50 from 49.74±3.36 to 97.82±8.61 g/mL). This is the first report on L. hongiaoensis EOs and significantly complements the composition and bioactivity of L. scandens EOs.